On the identity of Syntermes noiroti Krishna et al. 2013 (Isoptera: Termitidae: Syntermitinae) - Constantino, Reginaldo (Zootaxa, 2015)
Syntermes emersoni Grassé & Noirot 1949 is an available name of uncertain taxonomic status. It was published in a paper about the nest and biology of the African termite Sphaerotermes sphaerothorax (Sjöstedt 1911), with a brief description and a few illustrations (Grassé & Noirot 1949). The description is limited to the following words: “les mandibles du Syntermes emersoni n. sp. resemblent passablement à celles d’un Sphaerotermes mais sont plus grandes” [the mandibles of Syntermes emersoni n. sp. resemble those of Sphaerotermes but are larger]. Specimens examined by the authors and the localities from which they were collected are not mentioned. Although brief and limited, this description satisfies the requirements of availability (ICZN 1999, articles 10–12). Besides the inadequate description, the name is a junior primary homonym of Syntermes emersoni Snyder 1924 and cannot be used as valid.